PLANNING, PROGRAMMING, AND BUDGETING SYSTEM AS CORRELATES OF EFFECTIVE UNIVERSITY ADMINISTRATION IN SOUTH-EAST, NIGERIA (Scientific Journal of Educational Management, Research and law, 2025)
The study investigated planning, programming, and budgeting system as correlate of effective university education in South East, Nigeria. Correlational research design was used for the study. two research questions and two null hypotheses guided the study. All 411 respondents comprising 354 Heads of Department and 54 Deans of faculties/colleges in federal public universities in South-East was drawn through census sampling technique. Purposively all the population was used for the study. Planning, Programming and Budgeting System Questionnaire” (PPBSQ) and “Effective University Education Questionnaire” (EUEQ) were used form data collection. PPBSQ and EUEQ were validated by three experts from the field of educational administration and planning. Cronbach alpha method was used to determine the internal consistency of the instruments. Cluster by cluster reliability was determined of which cluster A yielded an index of .87, cluster B yielded an index of .73 for PPBSQ and .88 for (EUEQ). The 411 copies of the questionnaire were administered with the help of four briefed research assistants. Research questions were answered using Pearson Moment Correlation Coefficient, while the hypotheses were tested using Linear Regression analysis at 0.5 level of significance. Findings revealed that There was a high positive and no significant relationship between the extent Planning, Programming and Budgeting System (PPBS) and effective university Administration; it also finds that there was a high positive and no significant relationship between Strengths Weaknesses Opportunities and Threat Analysis (SWOT) and effective Administration. Based on the findings of the study, the researcher recommended that, administrators, Deans and HODs should provide a blueprint to strengthen program activities and improve weaknesses relating to efficiency of staff for effective university administration; that Deans and Hods should work on determining the proper sequence of the activities and critical path that would improve the advancement of university education administration